2003
DOI: 10.1088/0022-3727/36/19/002
|View full text |Cite
|
Sign up to set email alerts
|

Physical grounds for biological effect of laser radiation

Abstract: A new approach to the understanding of biological activity caused by low-intensity laser radiation, in which coherence is a factor of paramount importance, has been developed. It is based on the dipole interaction of gradient laser fields with cells, organelles and membranes. The laser intensity gradients in an object arise due to the interference of the light scattered by the tissue with the incident light beam (speckle formation). Apart from speckles, different types of light spatial modulation can be create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…We know at present that laser stimulation enables the seed cell to absorb and store radiant energy, which is then converted to chemical energy as a useable form in subsequent growth processes (Jamil et al, 2013). The above observation is substantiated by studies that confirmed the positive effects of laser radiation on enzyme activity at the early stages of germination (Chen et al, 2005b;Perveen et al, 2010;Rubinov, 2003).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We know at present that laser stimulation enables the seed cell to absorb and store radiant energy, which is then converted to chemical energy as a useable form in subsequent growth processes (Jamil et al, 2013). The above observation is substantiated by studies that confirmed the positive effects of laser radiation on enzyme activity at the early stages of germination (Chen et al, 2005b;Perveen et al, 2010;Rubinov, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…However, according to some authors, the best method to combine these goals is the use of physical treatments (Delibatowa and Ivanova, 2006;Flórez et al, 2007;Hernandez et al, 2010;Jun et al, 2007;Rochalska and Orzeszko-Rywka, 2008). In some researches opinion, presowing physical treatments of seeds are environmentally safe because they only modify biochemical and physiological processes in seeds, which, in consequence, accelerate seedling emergence and improve plant development (Chen et al, 2005a;Podleśny et al, 2012;Rubinov, 2003). Physical treatments, such as laser irradiation, do not replace chemical methods, but they can supplement them (Ouf and Abdel-Hardy, 1999;Vasilevski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are two main approaches towards multiple optical trapping: one based on strongly focused beams using the high numerical aperture objectives [6][7][8][9][10] and another based on interference methods when particles are trapped by interference field [11][12][13][14][15][16][17]. The first type systems were created by a number of means: by fast single beam scanning [6], by two counterpropagating Gaussian light beams [7], with methods of spatial light modulation, e.g., computer-generated holography [8] or generalized phase-contrast method [9], and with multiple light sources [10].…”
Section: Introductionmentioning
confidence: 99%
“…These advantages and possibilities make the interferometric technique a promising tool for the high speed operation with multicomponent suspensions and tissues. For instance, the selective capture and transportation of particles of different sizes by means of a moving interference field (the 'optical sweep-net' [17]) opens up interesting possibilities for biological applications. In particular, applications such as stimulation of blood transportation through microcapillaries, sorting and separation of lymphocytes, RBCs or other particles etc are expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation